Football in Spain, Passion or Violence? - Jiaoyue, Liu (2017)
Starting with the background and the developmente of World football, this paper makes a general analysis on the passion and violence in football. Then, focusing on the Spanish football, the essay reveals the respective expressions of passion and violence, analyzes in detail the reasons that generate violence and also offers some solutions to the problems. Finally, the article proposes measures to prevent the violence and keep the passion in order to make the Spanish football have a sustained and stable developmente.